Dança na educação infantil: uma possibilidade para a vivência da corporeidade - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
This research aimed to understand how classical dance, through the meanings of the phenomenon of corporeality, integrates children's daily lives, giving new meaning to their practices, spaces and times in the school educational process. This thesis intended to recognize that classical dance, as an artistic and rhythmic manifestation, developed through activities related to children's movements, can cooperate with the improvement of rhythm perception, with more participative, creative and critical children, that is, to the pursuit of children's citizenship. The study problematized with the following central question of the thesis: To what extent, the practices, spaces and times lived in dance in the school environment, having as assumption the phenomenon of corporeality¸ can cooperate with the sense and meaning of the perception of rhythm and of playfulness by and with children from a Merleau-Ponty perspective? The study contributes to the area of Education, Arts and Physical Education, with regard to didactic-pedagogical actions, which can collaborate in the training of education professionals, through the perception of the rhythm of different ways of reaching the child in his totality, evidencing the phenomenon of lived experience, the rhythm expressed in the child's movements, the conquest of autonomy and the formation of his own personality. As a methodological resource, it has a qualitative approach and uses a combination of bibliographic research and phenomenological research that is being developed with 10 children enrolled in the Casa da Criança kindergarten, as a way of providing contact with classical dance, one of the elements of rhythmic activities, through the proposal of dance-art-education from a playful perspective, their respective regular school teachers and the teacher linked to the dance project at school. It was a municipal public school, in the south central zone of Manaus, Center neighborhood. Data collection took place through participatory observations, field diary and interview with semi-structured scripts, which were carried out in three moments: the first, diagnosis and the others, carried out in the process of developing the meetings and finalizing the experiences. The results point to the creation of links between children and classical dance, expanding their knowledge, their potential and projecting a new vision of rhythmic activities with children at school.
Dance in early childhood education: a possibility for the experience of corporeality.
Keywords: CIENCIAS HUMANAS; LINGUISTICA, LETRAS E ARTES; Dança; Educação Infantil; Fenomenologia; Corporeidade